Being out inside discrimination of gay men in Iloilo City District jail male dormitory. - Labramonte, Vanessa J.
This study evaluated the experiences of Gay men in Iloilo City District Jail Male Dormitory (ICDJ-MD) in order to understand the situations of effeminate male in highly masculinised institutions. This study utilized the theory of West and Zimmerman?s (1987) ?Doing Gender? and Connell?s (2005) ?Hegemonic Masculinity?. This paper answered the research question, ?What are the experiences of discrimination encountered by gay men inside the Iloilo City District Jail Male Dormitory?? With this problem, the researchers examined the characteristics of gay inmates, experiences of discrimination, the forms and nature of discrimination and the people involved in the discrimination incidents. This study is a phenomenological research which focused on the experiences of gay men that display effeminate characteristics in ICDJ-MD. Thus the data present came from key informant through in-depth interviews. This research confirmed that indeed, gay men inside highly masculinised institution such as jails face various kinds of discrimination during detention. The domination of masculine men in the institution created a hostile environment for gay men and they were often discriminated.